THE SCOPE OF STUDYING THE CONCEPT OF HAPPINESS IN LINGUISTIC RESEARCH - Jumaniyozova Shakhlo Zohid kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores the scope of studying the concept of happiness in linguistic research, examining how language influences our perception and expression of emotions, particularly the nuanced experience of happiness. This article delves into the scope of researching the concept of happiness in linguistic studies, uncovering how language shapes our understanding and expression of emotions, particularly the complex and multifaceted experience of happiness. Real references are provided for further exploration of the topic.